Design, fabrication, and testing of a low-cost extrusion based 3D bioprinter for thermo-sensitive and light sensitive hydrogels. (2022) - Gusmão, Afonso; Sanjuan-Alberte, Paola; Ferreira, Frederico Castelo; Leite, Marco
Abstract: 3D bioprinting consists of the fabrication of complex biological structures, with animal cells cultured in vitro. It has enormous potential in developing animal tissues and organs for drug testing, regenerative medicine, and food products. Limitations on the technology include the cost of the commercial equipment's and the lack of flexibility required in R&D labs. Design, fabrication, and testing of a 3D bioprinter with temperature control and UV curing is presented. Printer acceptance tests were performed using hydrogel biomaterials including gelatine methacrylate (GelMA) and algae-derived polysaccharides. The designed equipment presents positive overall results, namely in printability, operation, and user-friendliness.